2015
DOI: 10.1007/s00259-014-2983-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bone marrow inflammation in patients with myelofibrosis: an 18F-fluorodeoxyglucose PET/CT study

Abstract: (18)F-FDG PET/CT is as a promising technique for the quantitation of bone marrow inflammation in myelofibrosis. Our data indicate that the intensity of bone marrow (18)F-FDG uptake decreases as bone marrow fibrosis increases. Further evaluation in prospective studies is required to determine the potential clinical impact and prognostic significance of PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 36 publications
1
24
1
Order By: Relevance
“…However, the imaging patterns in PMF of the respective radiopharmaceutical distribution are not similar. In a recent study, 18 F‐FDG PET/CT uptake was increased in the axial and distal skeleton when the degree of marrow fibrosis was low (grade I) and was rather mild when the degree of marrow fibrosis was high (grade III) . The authors concluded a significant inverse correlation between the extent of the metabolically active disease (axial skeleton and distal skeleton plus spleen) and time since the diagnosis of myelofibrosis .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the imaging patterns in PMF of the respective radiopharmaceutical distribution are not similar. In a recent study, 18 F‐FDG PET/CT uptake was increased in the axial and distal skeleton when the degree of marrow fibrosis was low (grade I) and was rather mild when the degree of marrow fibrosis was high (grade III) . The authors concluded a significant inverse correlation between the extent of the metabolically active disease (axial skeleton and distal skeleton plus spleen) and time since the diagnosis of myelofibrosis .…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study, 18 F-FDG PET/CT uptake was increased in the axial and distal skeleton when the degree of marrow fibrosis was low (grade I) and was rather mild when the degree of marrow fibrosis was high (grade III) [13]. The authors concluded a significant inverse correlation between the extent of the metabolically active disease (axial skeleton and distal skeleton plus spleen) and time since the diagnosis of myelofibrosis [13]. This reported inverse correlation pattern with 18 F-FDG PET/CT assessment contrasts with the 111 In-Cl 3 /SPECT/CT imaging we observed in the sMF patient (P5) of our series who was at an early phase of the disease and showing a lower fixation to 99m Tc nanocolloids and 111 In-Cl 3 at the distal skeleton.…”
Section: Inflammatory Versus Myelofibrotic Component Of Pmfmentioning
confidence: 92%
“…A recent study has demonstrated the feasibility of 18 F-FDG PET/CT for noninvasive visualization and quantitation of the extent and activity of bone marrow involvement in a cohort of patients before SCT (4). In that study, the metabolic activity of the bone marrow as determined by 18 F-FDG PET was significantly associated with the histopathologic grade of fibrosis, and the extent of disease on PET decreased with time after diagnosis.…”
mentioning
confidence: 79%
“…The final bone marrow SUV max results were produced by averaging the measurements for all 4 vertebrae. Lumbar bone marrow SUV max has previously been shown to be inversely correlated with the histopathologic grade of bone marrow fibrosis (4).…”
Section: Reference Standardmentioning
confidence: 99%
“…In a larger cohort including 57 patients, a complete or near complete resolution of bone marrow fibrosis at day +100 after reduced intensity allogeneic stem cell transplantation resulted in a favorable survival independently of IPSS risk score at transplantation and correlated with improved graft function and significantly less red blood cell and platelet transfusions [43]. Regression of bone marrow fibrosis is determined by bone marrow histology but can be monitored also by magnetic resonance imaging (MRI) [44] or more recently by positron emission tomography/computed tomography (PET/CT) [45] which is a promising technique for quantitation of bone marrow inflammation in myelofibrosis [46].…”
Section: Kinetics Of Bone Marrow Fibrosis Regressionmentioning
confidence: 99%